Case Report: Trastuzumab Treatment in Adenosquamous Carcinoma of the Extrahepatic Biliary Tract With Her-2 Amplification - Hong, Ye; Li, Xiaofen; Cao, Dan (Frontiers in Oncology, 2021)
Extrahepatic cholangiocarcinoma (ECC) is an uncommon and devastating malignancy that mainly consists of adenocarcinoma. Adenosquamous carcinoma is a rare histologic type and accounts for 2–5% of ECC. It reports that 3.6–8.5% of ECC patients carry Her-2 amplification. A 45-year-old woman was admitted to our hospital because of jaundice. Abdominal computerized tomography (CT) suggested extrahepatic biliary tract mass. The patient received surgery and pathological examination confirmed adenosquamous carcinoma. Fluorescence in Situ Hybridization (FISH) and Next-generation sequencing showed the tumor had Her-2 amplification. One month after the operation, CT demonstrated distant lymph nodes metastases (cT3N1M1, stage IV). The patient received gemcitabine and cisplatin combined with targeted therapy of trastuzumab. After three cycles of treatment, the evaluation of response was stable disease (SD). The progression-free survival of 1st line treatment (PFS1) reached 5 months with five cycles of treatment. After progression, the patient received three cycles of albumin-bound paclitaxel combined with S-1 and trastuzumab and concurrent chemoradiotherapy (S-1) because of serious backache. Now, the disease is stable, and the PFS of 2nd line treatment (PFS2) has reached 7 months.